Characteristics of the new financial strategist, master’s in finance students: Formando estrategas financieros - Guzmán-Ibarra, Luz-Elena; Joannis-Ortiz, León Antonio; Torralba-Chávez, Efraín (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this study was to determine if the characteristics of a strategist are acquired when completing a postgraduate degree, the population of interest was students of a master’s degree in finance, the sample was 87 students in quarterly groups for two consecutive years. Using a mixed approach methodology, a questionnaire, to complement the qualitative aspect, an inference was made on each result. The hypotheses “There are countless characteristics that the university student must develop, and the university student acquires 80% of the characteristics of a strategist at the University”. They are accepted, 89% acquire the characteristics at the University.